Reactions of ground magnesium limestone and gypsum in soils with variable-charge minerals - Shamshuddin, J.; Ismail, H. (John Wiley & Sons, 1995)
Ultisols and Oxisols in Malaysia are characterized by low pH and high Al, with their subsoils usually deficient in Ca, Mg, or both. An experiment, using polyvinyl chloride columns, was conducted to study chemical reactions in a representative Ultisol and Oxisol from Malaysia resulting from application of ground magnesium limestone (GML), gypsum, and their combinations. An increase in soil pH due to GML application in the Ultisol and the Oxisol resulted in an increase in negative charge on the soil surfaces in the zone of incorporation. Calcium was retained in that zone. In the gypsum-treated soils, some Ca moved into the underlying horizons. Negative charge in the Oxisol increased from 2.8 to 3.7 cmolc kg-1 by an application of 8 t gypsum ha-1 due to specific adsorption of SO4 on Fe oxides. An increase in pH of the Oxisol due to SO4 adsorption and OH desorption was also observed. There was an accumulation of NO3 in the subsoils of the Oxisol and Ultisol as a result of gypsum treatment. The NO3 was adsorbed by the positively charged oxides. Leachate pH values were high at the beginning of the experiment, but the values decreased with time and were higher in the Oxisol than the Ultisol. This was attributed to a lower Al concentration in the leachate of the Oxisol. Effective alleviation of topsoil Al toxicity and subsoil Ca or Mg deficiency would require the application of 2 t GML together with 1 to 2 t gypsum ha-1.